A method of evaluating online usability research: A case study of the Itaú Bank site - Fernandes, Fabiane Rodrigues [UNESP]; Paschoarelli, Luis Carlos [UNESP] (My University, 2013)
Through an assessment of the Itaú Bank website, this paper presents a methodology, based on ISO 9241 (NBR 9241-11:2002), to evaluate the effectiveness and efficiency of and satisfaction with online usability research. The final data were calculated as percentages based on score scale of SUS (ALBERT & TULLIS, 2008). Eight individuals participated in this study. Three were women and five were men, and their average age was 31 years. The results indicate that the interaction with the interface is satisfactory, but its efficacy must be improved. This paper also presents a simple method of measuring the level of performance of the interface. © 2013 IADIS.
Keywords: Evaluating; HCI; Method; Usability